CONNECTEDNESS IN INTUITIONISTIC FUZZY TOPOLOGICAL SPACES IN ŠOSTAK’S SENSE - El-Latif, A.A. Abd; Khalaf, Mohammed M. (Italian Journal of Pure and Applied Mathematics, 2015)
In this paper, we introduce various types of fuzzy connectedness in intuitionistic fuzzy topological spaces in view of Šostak's sense. The interrelationship between different notions of intuitionistic fuzzy connectedness are investigate. Also, we inspect some interrelations between these types of intuitionistic fuzzy connectedness together with the preservation properties under intuitionistic fuzzy continuous maps.